ENHANCING EDUCATORS' CAPACITY IN BANTUL: AI-DRIVEN LEARNING MEDIA FOR INNOVATIVE TEACHING IN ACHIEVING SDG 4 QUALITY EDUCATION - Roni Faslah; Ervina Maulida; Henry Eryanto; Sri Kartikowati; Adin Nur Rahman; Cherry Pramuditha; Noor Adila Abd. Raub (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This community service initiative, conducted on May 20, 2025, at SMP Negeri 3 Bantul, Yogyakarta, aimed to enhance the digital teaching capacity of secondary educators through the integration of Artificial Intelligence (AI) tools. Aligned with Sustainable Development Goal 4 (Quality Education), the program focused on equipping 40 teachers with hands-on experience using Eduaide and MagicSchool platforms designed to support adaptive content creation and classroom engagement. Implemented in four stages, preparation, training, implementation, and evaluation, the workshop provided live demonstrations, guided practice, and reflective discussions. Pre- and post-tests revealed a significant improvement in participants’ understanding, with average scores rising from 2.1 to 4.3 out of 5, and 85% of teachers achieving proficiency. Qualitative feedback highlighted increased confidence, enthusiasm, and readiness to apply AI in lesson planning and feedback automation. Challenges such as limited internet access and initial unfamiliarity with digital tools were mitigated through mentor support and accessible learning materials. This initiative demonstrated the effectiveness of structured, contextualized AI training in transforming pedagogical practices and recommends ongoing mentoring, peer collaboration, and scalable digital modules for sustained impact. The project illustrates that even short-term interventions can meaningfully empower educators and promote inclusive, future-ready education in under-resourced communities.